2016
DOI: 10.15244/pjoes/63297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and RNA-seq Transcriptome Analysis of Tricholoma matsutake from Sichuan Province, China

Abstract: The sequences of the internal transcribed spacer (ITS) regions of ectomycorrhizal fungi collected from Sichuan Province were analyzed using a PCR primer pair specific to T. matsutake. The amplified fragments were sequenced and compared with each other to build a phylogenetic tree. The mRNA deep sequencing approach was adopted to identify differentially expressed T. matsutake genes among the transcriptomes developed from a Xiaojin sample. A phylogenetic analysis of the aligned sequences was performed using maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The neighbor-joining (NJ) phylogenetic tree showed that the JrDof genes are divided into six subfamilies (A to F) in Persian walnut (Fig. 1), and according to previous studies, this classification was performed [1,34,55]. The Dof members from Arabidopsis and rice were classified into four groups (a, b, c and d), which is slightly distinct from the present phylogenetic analysis with Dofs of J. regia [61].…”
Section: Dof Gene Family Identification and Phylogenetic Relationshipmentioning
confidence: 51%
See 1 more Smart Citation
“…The neighbor-joining (NJ) phylogenetic tree showed that the JrDof genes are divided into six subfamilies (A to F) in Persian walnut (Fig. 1), and according to previous studies, this classification was performed [1,34,55]. The Dof members from Arabidopsis and rice were classified into four groups (a, b, c and d), which is slightly distinct from the present phylogenetic analysis with Dofs of J. regia [61].…”
Section: Dof Gene Family Identification and Phylogenetic Relationshipmentioning
confidence: 51%
“…We implemented a profile hidden Markov model (HMM) in HMMER v. 3 [29]. The phylogenetic NJ tree was constructed with the pairwise deletion of 1000 bootstraps and a Poisson model [34]. To search for the presence of potential domains, the Pfam web server (http://pfam.xfam.org/) [33], was used, and 39 Dof protein sequences were detected.…”
Section: Dof Transcription Factors Identification In J Regiamentioning
confidence: 99%